Escaping poverty traps and unlocking prosperity in the face of climate risk: Lessons from Index-Based Livestock Insurance - Jensen, Nathaniel D.; Fava, Francesco P.; Mude, Andrew G.; Barrett, Christopher B.; Wandera-Gache, Brenda; Vrieling, Anton; Taye, Masresha; Takahashi, Kazushi; Lung, Felix; Ikegami, Munenobu; Ericksen, Polly J.; Chelanga, Philemon; et al. (Cambridge University Press, 2024)
This Element outlines the origins and evolution of an international award-winning development intervention, index-based livestock insurance (IBLI), which scaled from a small pilot project in Kenya to a design that underpins drought risk management products and policies across Africa. General insights are provided on i) the economics of poverty, risk management, and drylands development; ii) the evolving use of modern remote sensing and data science tools in development; iii) the science of scaling; and iv) the value and challenges of integrating research with operational implementation to tackle development and humanitarian challenges in some of the world's poorest regions.